2013
DOI: 10.1017/s0022109013000513
|View full text |Cite
|
Sign up to set email alerts
|

Stock Price Jumps and Cross-Sectional Return Predictability

Abstract: We identify large discontinuous changes, known as jumps, in daily stock prices and explore the role of jumps in cross-sectional stock return predictability. Our results show that small and illiquid stocks have higher jump returns to the extent that cross-sectional differences in jumps fully account for the size and illiquidity effects. Based on value-weighted portfolios, jumps also account for the value premium. On the other hand, jumps are not the cause of momentum or net share issue effects. The findings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
49
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 52 publications
11
49
2
Order By: Relevance
“…14 consistent with Jiang and Yao (2013) who show that small stocks tend to have higher jump returns than large stocks. The negative jump-firm size relationship found here and in Jiang and Yao (2013) could be explained by prior literature (see, for example, Bhushan, 1989) showing that small firms tend to have low analyst followings because of frequent credit-constrained situations.…”
Section: Defining Systematic Cojumpssupporting
confidence: 77%
“…14 consistent with Jiang and Yao (2013) who show that small stocks tend to have higher jump returns than large stocks. The negative jump-firm size relationship found here and in Jiang and Yao (2013) could be explained by prior literature (see, for example, Bhushan, 1989) showing that small firms tend to have low analyst followings because of frequent credit-constrained situations.…”
Section: Defining Systematic Cojumpssupporting
confidence: 77%
“…We include Size, Book-to-Market, Momentum and Illiquidity. These variables have been shown to be priced in the cross-section of stock returns (Jegadeesh & Titman, 1993;Amihud, 2002;Fama & French, 2008;Jiang & Yao, 2013). We further include two jump measures since recent studies have shown that jumps are an important factor in the crosssection of stock returns.…”
Section: B Explaining Long Memory With Firm Characteristicsmentioning
confidence: 99%
“…We further include two jump measures since recent studies have shown that jumps are an important factor in the crosssection of stock returns. Jiang & Yao (2013) analyze the predictability of cross-sectional stock returns and find that once controling for jumps firm characteristics such as size and liquidity are no longer predictive. Kelly & Jiang (2014) and Cremers et al (2015) show that the sensitivity of stocks to market tail and jump risk helps to explain the crosssectional variation in expected returns.…”
Section: B Explaining Long Memory With Firm Characteristicsmentioning
confidence: 99%
“…For instance, Jiang and Yao (2013) find that illiquid stocks have higher daily jump returns in the cross-section. Bradley et al (2014) find that up to 70% of jumps in equity prices cannot be explained by salient news arrivals, suggesting that trading frictions play an economically important role in causing large stock price changes.…”
Section: Introductionmentioning
confidence: 99%